Fontan Circulation Associated Organ Abnormalities Beyond the Heart, Lungs, Liver, and Gut: A Systematic Review - Ritmeester, Evi; Veger, Veerle A.; van der Ven, Jelle P. G.; van Tussenbroek, Gabrielle M. J. W.; van Capelle, Carine I.; Udink ten Cate, Floris E. A.; Helbing, Willem A. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Patients with a Fontan circulation are at risk for sequelae of Fontan physiology during follow-up. Fontan physiology affects all organ systems and an overview of end-organ damage is needed. Methods We performed a systematic review of abnormalities in multiple organ systems for patients with a longstanding Fontan circulation. We searched online databases for articles describing abnormalities in multiple organ systems. Cardio-pulmonary abnormalities, protein losing enteropathy, and Fontan associated liver disease have already extensively been described and were excluded from this systematic review. Results Our search returned 5,704 unique articles. After screening, we found 111 articles relating to multiple organ systems. We found abnormalities in, among others, the nervous system, pituitary, kidneys, and musculoskeletal system. Pituitary edema—relating to the unique pituitary vasculature- may affect the thyroid axis. Renal dysfunction is common. Creatinine based renal function estimates may be inappropriate due to myopenia. Both lean muscle mass and bone mineral density are decreased. These abnormalities in multiple organ systems may be related to Fontan physiology, cyanosis, iatrogenic factors, or lifestyle. Conclusions Health care providers should be vigilant for hypothyroidism, visual or hearing deficits, and sleep disordered breathing in Fontan patients. We recommend including cystatin C for assessment of renal function. This review may aid health care providers and guide future research. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021232461, PROSPERO, identifier: CRD42021232461.